1980
DOI: 10.1042/bj1850679
|View full text |Cite
|
Sign up to set email alerts
|

The development of a radioimmunoassay for Tamm–Horsfall glycoprotein in serum

Abstract: The Tamm-Horsfall glycoprotein prepared by salt precipitation from urine was found to comprise a heterogeneous collection of aggregates. These could be disaggregated with 8m-urea, following which chromatography on a column of Bio-Gel A.15m yielded a homogeneous glycoprotein of mol.wt. 73000 together with several unidentified impurities. Gel filtration of normal plasma showed the glycoprotein to exist predominantly in a form that is eluted identically with the purified preparation. In one case, material of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…It was originally isolated from human urine by Tamm and Horsfall who noted its ability to inhibit viral haemagglutination [1]. It is present in large quantities in the urine and is also found in plasma where its presence has been demonstrated by Avis [2] using a radio-immunoassay and confirmed by Dawnay et al [3]. It is the major constituent of hyaline casts [4] and is present in the matrix of most types of renal calculi [5].…”
Section: Introductionmentioning
confidence: 94%
“…It was originally isolated from human urine by Tamm and Horsfall who noted its ability to inhibit viral haemagglutination [1]. It is present in large quantities in the urine and is also found in plasma where its presence has been demonstrated by Avis [2] using a radio-immunoassay and confirmed by Dawnay et al [3]. It is the major constituent of hyaline casts [4] and is present in the matrix of most types of renal calculi [5].…”
Section: Introductionmentioning
confidence: 94%
“…A competitive liquid-phase ra dioimmunoassay was used. Rat THP was iodinated us ing the chloramine-T method as described elsewhere [3] for human THP. The assay buffer contained 0.052 M phosphate, 0.01 M EDTA.…”
Section: Measurement O F Thpmentioning
confidence: 99%
“…Tamm-Horsfall glycoprotein (THP) has been detected in urine [1], serum [2][3][4] and kidney [5][6][7][8] of a variety of mammalian spe cies. Excreted at a daily rate of 50-100 mg in man, it is the most abundant urinary protein [9].…”
Section: Introductionmentioning
confidence: 99%
“…We developed an ELISA for the microdetermination of THGP. This assay required no special equipment and safely handled many samples at the same time with the same sensitivity as that of radioim munoassay described by Avis [5] and Dawnay et al [6], Recently, Avis [10] and Hunt et al [11] reported ELISA techniques for the quantitation of serum THGP using a different type of antigen assay. In the present study, our assay had approximately the same sensitivity as their ELISA methods making it useful for determining THGP levels in routine blood samples.…”
Section: Discussionmentioning
confidence: 99%